Pengaruh Content Marketing terhadap Minat Beli Produk Instaperfect pada followers akun TikTok @Instaperfect_id melalui Attitude Towards The Brand dan Attitude Towards The Advertisement - Zain, Nada Khalishah; Wahyudin, Uud; Setiaman, Agus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rapid growth of the cosmetic industry in Indonesia has led to unavoidable competition. The intense business competition at the moment poses a challenge for companies to stay competitive in the industry. This competition forces manufacturers to compete in creating innovative and varied products to satisfy their consumers. Therefore, companies need to pay more attention to the interests and needs of consumers in marketing their products to influence consumer purchasing interest. This study aims to analyze the influence of Instaperfect marketing content on the purchasing interest of Instaperfect products through brand attitude and attitude towards advertisements. The research respondents were taken from 84 followers of the TikTok account @Instaperfect_id who had commented on posts from March 2023 to May 2023. Data collection methods used a questionnaire with a scale from one to five (1-5). The analysis method used was path analysis to test hypotheses and to test the influence of mediating variables that mediate between independent and dependent variables. The results of the study show a significant influence of marketing content on purchasing interest, brand attitude, attitude towards advertisements, purchasing interest through brand attitude, and purchasing interest through attitude towards advertisements.